NUTRITIONAL INTAKE LEVEL OF SEPAKTAKRAW ATHLETES IN SEKOLAH OLAHRAGA NEGERI SRIWIJAYA (SONS) PALEMBANG SOUTH SUMATRA - Iyakrus Iyakrus (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to find out 1) what is the level of nutrition intake of sepaktakraw athletes in Sekolah Olahraga Negeri Sriwijaya Palembang, 2) is the level of nutritional needs of athletes sepaktakraw in Sekolah Olahraga Negeri Sriwijaya Palembang sufficient. The method used in this research is descriptive method with survey technique. The subjects of the study were 13 sepaktakraw athletes of Sekolah Olahraga Negeri Sriwijaya Palembang, with questionnaire data collection techniques, interviews and observations. The results of the study 1) the calorie nutritional intake needed by the Sekolah Olahraga Negeri Sriwijaya Palembang sepaktakraw athletes is 3559.6 Kcal, while the calories obtained are only 3204.0 calories. 2) Calorie needs of the Sepaktakraw athletes in Sekolah Olahraga Negeri Sriwijaya Palembang have not been fulfilled. From the results of the study it can be concluded that 1) the level of nutrient intake of sepaktakraw athletes in Sekolah Olahraga Negeri Sriwijaya Palembang does not meet the standards of athletic nutrition, 2) the level of nutritional needs is not yet in accordance with the needs of the sepaktakraw sports branch.